2008
DOI: 10.1111/j.1365-2486.2008.01593.x
|View full text |Cite
|
Sign up to set email alerts
|

Large annual net ecosystem CO2 uptake of a Mojave Desert ecosystem

Abstract: The net ecosystem CO 2 exchange (NEE) between a Mojave Desert ecosystem and the atmosphere was measured over the course of 2 years at the Mojave Global Change Facility (MGCF, Nevada, USA) using the eddy covariance method. The investigated desert ecosystem was a sink for CO 2 , taking up 102 AE 67 and 110 AE 70 g C m À2 during 2005 and 2006, respectively. A comprehensive uncertainty analysis showed that most of the uncertainty of the inferred sink strength was due to the need to account for the effects of air d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
159
3
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(174 citation statements)
references
References 74 publications
(142 reference statements)
7
159
3
5
Order By: Relevance
“…The effects of self-heating can be corrected for in post-processing (Burba et al, 2008), however while some studies found these corrections to improve the correspondence with concurrent closed-path CO 2 flux measurements (Burba et al, 2006(Burba et al, , 2008Grelle and Burba, 2007;Järvi et al, 2009), others did not (Wohlfahrt et al, 2008a;Haslwanter et al, 2009). The reasons for these mixed results are unclear at present; they may be partly attributed to differences in environmental conditions (Haslwanter et al, 2009), partly to the deployment of the open-path analyser.…”
Section: Eddy Covariance Flux Datamentioning
confidence: 58%
“…The effects of self-heating can be corrected for in post-processing (Burba et al, 2008), however while some studies found these corrections to improve the correspondence with concurrent closed-path CO 2 flux measurements (Burba et al, 2006(Burba et al, , 2008Grelle and Burba, 2007;Järvi et al, 2009), others did not (Wohlfahrt et al, 2008a;Haslwanter et al, 2009). The reasons for these mixed results are unclear at present; they may be partly attributed to differences in environmental conditions (Haslwanter et al, 2009), partly to the deployment of the open-path analyser.…”
Section: Eddy Covariance Flux Datamentioning
confidence: 58%
“…Often the downward flux of CO 2 is not equal to carbon accumulation in plants or soils [Jasoni et al, 2005;Luo et al, 2007;Wohlfahrt et al, 2008]. For instance, in European grasslands DIC leaching out of the ecosystem can account for a large portion (22% or 24 g C m À2 yr À1 ) of the net ecosystem exchange of carbon (NEE) [Kindler et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the techniques currently available for correcting the surface heating effect are only suitable for vertical sensors, and thus would overestimate the bias for the titled sensors. Besides, directly applying this correction seems unwarranted at present because the results of the correction varied greatly among different experimental sites (Burba et al, 2008;Wohlfahrt et al, 2008;Haslwanter et al, 2009). For these reasons, we assumed that the self-heating effect was of minimal importance in our case.…”
Section: Uncertainties In Eddy Covariance Neementioning
confidence: 99%